Mini-review antimicrobial smart materials: the future’s defense against wound infections - Monroe, Mary Beth Browning; Fikhman, David A. (Frontiers in Biomaterials Science, 2023)
The overuse of antibiotics to treat bacterial infections along with bacteria's propensity to form biofilm communities has resulted in an alarming rise in drug-resistant microbes. Current approaches to infection surveillance and biofilm clearance in wounds are severely limited, requiring new biomaterials-based strategies to address this problem. To that end, a range of antimicrobial smart materials have been developed that change their properties in response to bacteria-induced external stimuli, providing tools with an additional level of complexity for defending against microbes. Researchers have tried to tackle this issue using materials that respond to the unique pH, temperature, and enzymatic changes that are induced by bacteria in wounds. These environmental responses are coupled with mechanisms to kill surrounding bacteria and/or to signal infection. For example, bacteria-responsive biomaterial solubilization (transition from non-solubilized solid material to solubilized liquid solution), swelling (volumetric increase due to absorption of surrounding media), de-swelling, degradation, or shape change can be coupled with drug release and/or activation or biofilm disruption, inhibition, or destruction. These materials provide a foundation for future work and improvements related to enhanced infection surveillance, increased specificity of infection response, and effective clearance of biofilms from wound surfaces.